Did the 2008 financial crisis affect Chinese import and export industry and foreign exchange rate risk? - TAN, JUN (2014)
This paper researched the impact of the 2008 financial crisis on Chinese export and import through the channel of exchange rate. It also investigated the influence of financial crisis on foreign exchange rate risk. The research period is from August 2006 to December 2013.The paper selected the United States and Europe zone as export and import research objects, then accordingly, it chose the USD/RMB and Euro/RMB exchange rate as exchange rate research objects. Firstly, the paper used the linear regression method proved that the financial crisis have negative impact on both two exchange rates. Then it employed random walk model to forecast the exchange rate movements. The time series forecasting model worked and showed the two exchange rate follow random walk. It also illustrated that the USD/RMB and Euro/RMB exchange rate will forever affected by the financial crisis. Moreover, the USD/RMB and Euro/RMB exchange rate markets are weal form inefficient. The study certified the impact of exchange rate on Chinese export and import: both USD/RMB and Euro/RMB exchange rate negative affect the export and import but the spurious issue need to be more careful. The research results in this dissertation are in line with most empirical studies.